PPM BENGKEL DAN TOKO SEPEDA DESTROYER BIKE KOTA SURABAYA - Atmojo, Suryo; Utami, Ruli; Dewi, Suzana; Widhiyanta, Nurwahyudi; Sholikin, Nur Ali (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Destroyer Bike Founded in 2020 by Mr. Ario Zanuar, a spare part sales service business and bicycle service workshop based on Jl. Medokan Semampir Indah, Surabaya City, East Java, Indonesia. Mr. Ario Zanuar started working in the bicycle repair business since the 2020 pandemic, with a focus on servicing folding bicycles, mountain bicycles, hybrid bicycles, call bicycles and fixie bicycles. In the first year, Destroyer Bike focused on on-site or in-store bicycle services only. However, over time, call services have gradually developed. The problem with this partner is the high competition in the bicycle spare part sales industry and bicycle repair shops which are quite competitive, especially in densely populated areas such as the city of Surabaya, so they need to compete with other bicycle repair shops. The second problem is the workshop service equipment which is still incomplete, due to the condition of the workshop which has just been started. The next problem is seasonality and fluctuations in demand in the bicycle repair business can vary depending on the season. Summer usually has higher demand as many people use bicycles for exercise or to cycle to work. However, in winter or bad weather, demand for bicycles decreases, while demand for bicycle repair services increases. Based on these problems, this service offers a solution for using promotional media with web profiles and social media to give a good impression to potential customers. By having an informative and attractive web profile, service companies can increase credibility, expand business reach, provide information that is easily accessible to customers, as well as branding and identity. The next solution is the use of market places for wider market access, increasing visibility, strengthening consumer trust, ease of transactions, simplifying the sales process, low operational costs and customer service support. The next solution is providing assistance with bicycle service equipment and training in the use of information systems to schedule bicycle service call visits. The method used in this service is Community Empowerment. This method aims to empower communities by providing the knowledge, skills and resources needed to overcome the problems they face. This can be done through training, workshops or specially designed educational programs